PERILAKU MENYONTEK SISWA DITINJAU DARI KECENDERUNGAN LOCUS OF CONTROL - Musslifah, Anniez Rachmawati (TALENTA, 2012)
Cheating behavior is one of education phenomena that not only often but also always appearing   in the teaching learning process. One of the factor which  influence cheating behavior is the tendency of locus of control. The population of the research is Widodaren I senior high school students while the number of sample is 70 students. The sampling technique used cluster random sampling. Data collecting method used locus of control and cheating behavior scale.  In analizing data  Annava two line was conducted . The result shows that there is a significant differences to students behavior observed from the tendency of locus of control with the value of R2is 0.079 and FA is 5.961 with p=0.016 (p<0.05). Moreover, the result also shows that there is not a significant differences in cheating behavior observed from gender with the value of F is 2.813  and  p=0.094 (p>0.05). The result means variable locus of control covers internal aspect can be become predictor to predict or measure cheating behavior.